Redirected walking method considering the interaction between users - Ri, Sho; Matsumoto, Keigo; Narumi, Takuji; Kuzuoka, Hideaki (Frontiers in Virtual Reality, 2025)
Redirected walking (RDW), which enables users to walk in a larger virtual space than the physical space, is being applied to enable multiple people to perform activities in a vast VR space while avoiding collisions with each other in the same real space. A method called AFP-RDW, which uses scalar potentials, has been proposed as a control method for RDW. However, while the scalar potential can control the user’s position, it cannot control the user’s orientation. Therefore, APF-RDW cannot be directly used for interactions between users in situations where multiple people experience VR. In this study, we proposed a method to guide users to a position and posture where they can interact with each other by introducing artificial vector potentials (AVF) and walking path simulation. To verify the proposed method, we conducted simulation experiments assuming interaction with objects and other users, and the results suggest that users can interact with objects and other users in both physical and virtual spaces, even in VR experiences where multiple people share the physical and virtual spaces. The results suggest that users may be able to interact with objects, other users, and other users in VR experiences where multiple people share the physical and virtual spaces, respectively.